The Role of Iron for Supporting Children’s Growth and Development - Bernie Endyarni Medise (Indonesian Nutrition Association, 2021)
According to the World Health Organization (WHO), Iron Deficiency (ID) affects around 2 billion people worldwide. Early childhood ID has been associated with permanent cognitive deficits associated with CNS structural, metabolic impairment, growth retardation, impaired immune response, psychological abnormalities, and behavioral delays. This literature review will focus on the important role of iron in child growth and development. Iron is necessary for various cellular processes in the growing brain especially when it comes to memory and learning. Children with early ID show cognitive deficits that persist; however, prompt iron treatment soothes the problem. A chronic ID group reported substantially lower scores of vocabularies, ambient sound perception, and motor measurements in a recent study relative to infants with normal nutritional iron status at 6 months and 14-18 months. Children's iron requirement differentiates based on individual age. The daily iron requirement for one- to three-year-old children is 7 mg. Some risk factors of infants and toddlers in developing ID are insufficient food intake, poor bioavailability, reduced absorption, increase demand, increase losses, cow’s milk enteropathy hookworm infection, and maternal gestation. Iron plays an important role in promoting children's growth and development. Physical health and nutrition are important in the first two years of life. Children who are unable to achieve iron adequacy will possibly show permanent cognitive deficit and impaired motor growth. Thus, iron supplementation may only be successful in early prescription after diagnosing iron deficiency.